Private equity takeovers in Australia : three essays on motivation, managerial share ownership and governance effects - Rashid, Mamunur (Curtin University, 2012)
Private equity transactions have grown considerably during the last few years. With an increase in the growth and size of this market, it has become increasingly important to understand the economic forces behind these transactions. Extant literature lacks adequate research in this area and studies on the Australian context are scarce. This thesis is a rigorous empirical investigation of the interaction of three aspects of Australian private equity transactions; namely, information asymmetry and undervaluation, managerial shareholdings and corporate governance.Using a unique hand-collected dataset and a matched-sample of firms from 1990 to 2010, I developed and tested a predictive choice model that distinguishes firms going private through private equity from firms that do not. The empirical results show that market undervaluation, rather than information asymmetry, is the dominant factor in going private. Further, it was found that institutional holding is a significant deterrent to private equity investment decision.I also analysed the importance of high managerial ownership and undervaluation as determinants in private equity deals in Australia. Results show that firms taken over by private equity firms suffer from market undervaluation and have high managerial shareholdings, a condition which is likely to motivate managers to take their firms private. Confirming extant theoretical arguments of non-linear relationship between managerial shareholding and firm value, supporting evidence was found in the Australian market.Finally, I investigated the effect of managerial shareholdings and corporate governance on private equity takeovers. Evidence is presented of a significant nonlinear relationship between managerial ownership and firm-specific governance characteristics. This evidence indicates that corporate governance practices have a significant impact on a firm’s choice of going private. In addition, evidence is provided that market for corporate control is active in Australia and plays a disciplinary role as, and when, necessary.